PENINGKATAN HUBUNGAN OPTIMAL MULTIKULTUR MAHASISWA TERHADAP PENGEMBANGAN KECERDASAN BUDAYA CQ - Santi Septiana (Jurnal Riset Bisnis Indonesia, 2014)
The objective of this study is to examine the effect of optimal multicultural contact students andexpectancy disconfirmation on the development of cultural intelligence (CQ). This study also examinesthe effect of expectation disconfirmation as intervening variable on the relationship between optimalmulticultural contact student and the development of cultural intelligence (CQ). Moreover, to examinethose variables, researches was using students that consists of Tolaki, Muna, Bugis, Buton , Java,Bungku, Tator, Makassar, Wolio, Manado, Wawonii, Menui and China. Furthermore, in taking samplethe researcher was used census method with spread questioners to 119 respondents which all ofthem are the students of Magister Management 4th semester at Sultan Agung Islamic University.Meanwhile, the technique of analysis data was used SPSS. The results indicate that optimalmulticultural contact students and expectancy disconfirmation influenced the development of culturalintelligence (CQ) significantly. But the expectancy disconfirmation is not mediated the relationshipbetween optimal multicultural contact students and the development of cultural intelligence (CQ).Keywords: Optimal Multicultural Contact Students, Expectancy Disconfirmation, the Developmentof Cultural Intelligence CQ